2019
DOI: 10.1111/pai.13096
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial‐derived butyrate is inversely associated with IgE responses to allergens in childhood asthma

Abstract: Background A comprehensive metabolomics‐based approach to address the impact of specific gut microbiota on allergen sensitization for childhood rhinitis and asthma is still lacking. Methods Eighty‐five children with rhinitis (n = 27) and with asthma (n = 34) and healthy controls (n = 24) were enrolled. Fecal metabolomic analysis with 1H‐nuclear magnetic resonance (NMR) spectroscopy and microbiome composition analysis by bacterial 16S rRNA sequencing were performed. An integrative analysis of their associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 36 publications
5
76
1
3
Order By: Relevance
“…Lower abundance of genera Faecalibacteria, Roseburia, increased abundance of genus Clostridium in asthmatic children [38] Infants at high risk for asthma, gut microbiome…”
Section: The Airway Microbiome In Children: Influence On Asthma Develmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower abundance of genera Faecalibacteria, Roseburia, increased abundance of genus Clostridium in asthmatic children [38] Infants at high risk for asthma, gut microbiome…”
Section: The Airway Microbiome In Children: Influence On Asthma Develmentioning
confidence: 99%
“…This bacterial dysbiosis of the gut microbiome was confirmed in another study by the same group of authors, showing that opposing shifts in the relative abundance of Lachnospira and Clostridium neonatale in the first 3 months of life was associated with asthma development at preschool age [37] ( Table 2). In a recent metabolomics-based approach, stool samples from children aged 4 to 7 years with asthma were compared to healthy children, with a focus on gut metabolites such as amino acids or butyrate [38]. Taxonomic classification showed that among gut bacteria, the phyla Firmicutes (67.8%), Actinobacteria (20.7%), and Bacteriodetes (8.4%) accounted for 97% of all analyzed sequences.…”
Section: The Role Of the Gut-lung Axis In Airway Microbiome And Asthmamentioning
confidence: 99%
“…In a recent paediatric study, Escherichia was one of three significantly predominant genera in children with asthma compared with healthy controls. 10 Furthermore, in a recent adult study, Escherichia was one of two genera that discriminated asthmatics with fixed airway obstruction from those with no airway obstruction. 11 These results are in line with our findings, potentially indicating that the abundance of Escherichia in particular may play a role in the early development of asthma.…”
Section: Gut Microbiota In Wheezing Preschool Children and The Associmentioning
confidence: 99%
“…Epidemiological observations provide a mountain of evidence in proving the link between asthma and environmental microbial and parasite exposure. 60 106 107 108 109 110 Human fecal bacteria transplantation, probiotic therapy 111 112 and parasite immunotherapy 76 113 used in clinical trials, and mouse model research 114 115 have enhanced our understanding of the interconnection between environmental microbes, 116 symbionts, 117 118 119 120 121 122 123 and asthma. The available data support the negative correlation between exposure to farms and rural environmental microorganisms in early life and that the incidence of allergic asthma and the specific exposure time window could be critical.…”
Section: Future Research Directionsmentioning
confidence: 99%